KEKERASAN DALAM RUMAH TANGGA (KDRT) (Studi Kasus Terhadap Kekerasan Fisik Pada Istri Dalam Keluarga di Jorong IV Koto Kecamatan Kinali Kabupaten Pasaman Barat) - Riyanti, Oma - (Pendidikan Sosiologi, 2014)
Violence against woman is man action that do certain strength so that give rise to physical suffering. According to articles of law No. 23 of 2004 on the elimination of domestic violence, violence in household is physical violence, psychological violence, violence sexual and neglect feel hurt, fall ill or trauma. Violence in household Jorong IV Koto subdistrict Kinali total there are seven house holds, wife of violence experienced an unnatural violence committed by husbands like slap, spaking and push against the wall because wife have human rights to life happily not suffering. The research design is gualitalive approach mean while type of the research is descriptive. The research informants are seven wifes. The informants choose by using purposive sampling, the data is accumulated by interview and dokumentation. Analisis object is individual, used first dat and second data. The data analysis is used qualitative analysis.